ISOLATION AND IDENTIFICATION OF SECONDARY METABOLITES OF BLACK BETEL (Piper betle L. var Nigra) - Junairiah Junairiah; Ni’matuzahroh Ni’matuzahroh; Nabilah Istighfari Zuraidassanaaz; Lilis Sulistyorini (Jurnal Kimia Riset, 2018)
AbstractPiper betle L. var Nigra commonly known as black betel have a potential as drug raw materials. The leave of black betel  can be used to resist bleeding so as to accelerate the healing of wounds on the skin, sputum, other uses are for epistaxis, as well as for dialysis, asthma, bronchitis, cough, and high blood pressure. Many uses of black betel leaves make it interesting to learn its metabolites compounds by phytochemical screening. So, this research aimed  to isolate and identificate secondary metabolites of Piper betle L. var Nigra. This research used three kind of organic solvents, there were methanol, ethyl acetate, and n-hexane. Several screening tests were used to isolate and identificate the phytochemical compound, including screening of alkaloids, terpenoids/steroids, flavonoids, polyphenols, tannins, and saponins. The results showed that methanol extract of black betel leaves contained of alkaloids, terpenoids/steroid, flavonoids, polyphenols and tannins compounds. The ethyl acetate extract of black betel leaves contained of terpenoids/steroid, flavonoids and tannins compounds. The n-hexane extract of black betel leaves contained of terpenoids/steroid. The methanol extract of Piper betle L. var Nigra contained more secondary metabolites than n-hexane and ethyl acetate extracts. Keywords : methanol ; Phytochemical screening ; Piper betle L. var Nigra.